2015
DOI: 10.1159/000441600
|View full text |Cite
|
Sign up to set email alerts
|

Role of Focal Therapy with High-Intensity Focused Ultrasound in the Management of Clinically Localized Prostate Cancer

Abstract: Overtreatment of prostate cancer (PC) remains one of the main burdens in uro-oncology. Focal therapy may be a reasonable alternative with less side effects and morbidity. Application of high-intensity focused ultrasound (HIFU) induces immediate and irreversible coagulation. The treatment leads to consecutive necrosis with sharply delineated margins, making HIFU a promising tool for the focal therapy of localized PC. Unlike radiation, the treatment leaves no collateral damage outside of the heated tissue, allow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…Four systematic reviews of HIFU in the treatment of prostate cancer have been published. [21][22][23][24] Warmuth et al 21 identified 20 uncontrolled prospective case series, totalling 3021 patients (2794 primary therapy and 227 salvage therapies). They concluded that, for all HIFU procedures, the biochemical disease-free rate at 1, 5 and 7 years was 78-84%, 45-84% and 69%, respectively.…”
Section: High-intensity Focused Ultrasoundmentioning
confidence: 99%
See 2 more Smart Citations
“…Four systematic reviews of HIFU in the treatment of prostate cancer have been published. [21][22][23][24] Warmuth et al 21 identified 20 uncontrolled prospective case series, totalling 3021 patients (2794 primary therapy and 227 salvage therapies). They concluded that, for all HIFU procedures, the biochemical disease-free rate at 1, 5 and 7 years was 78-84%, 45-84% and 69%, respectively.…”
Section: High-intensity Focused Ultrasoundmentioning
confidence: 99%
“…Longer-term effects on QoL are unknown. Kuru et al 24 conclude that HIFU treatment, and especially focal ablation of tumour foci, seems to be a safe alternative to standard treatment, with fewer side effects. The oncological results seem satisfactory but need further follow-up to validate this practice of PCa control.…”
Section: High-intensity Focused Ultrasoundmentioning
confidence: 99%
See 1 more Smart Citation
“…It is now commonly believed that the index lesion, defined as the largest lesion detected at imaging, is the one that will be responsible for disease progression . To avoid overtreatment of these lesions and reduce costs, alternative curative therapies that offer rates of cancer control equivalent or better to radical prostatectomy and external radiotherapy are being attempted with greater frequency, particularly in Europe. Such alternative focal therapy treatments offer the advantage of decreased morbidity and therefore an improved quality of life .…”
mentioning
confidence: 99%
“…Although a variety of treatment options, such as radical prostatectomy, external beam radiation therapy, brachytherapy, and active surveillance are available for patients with low- and intermediate-risk prostate cancer, focal therapy might emerge as a new, minimally-invasive, and oncologically effective treatment modality due to the improvements of prostate cancer imaging with multiparametric MRI. Timor Kuru and colleagues summarize the current scientific and clinical evidence of the various technologies of focal prostate cancer treatment [2]. For a long time external beam radiation therapy has been the standard therapy for high-risk prostate cancer.…”
mentioning
confidence: 99%